Spatially integrative metrics reveal hidden vulnerability of microtidal salt marshes - Neil K. Ganju (Nature Portfolio, 2017)
Point measurements have historically been used to assess salt marsh vulnerability; however, these metrics do not integrate over the necessary spatiotemporal scales. Here, the authors show that two geomorphic-based, spatiotemporally integrative metrics reveal vulnerability not captured by traditional metrics.